m6A RNA modification and myeloid-derived suppressor cells: mechanistic insights and clinical prospects - Li, Chunhong; Jiang, Xiulin; Yuan, Yixiao; Chen, Xi; Pu, Shanrui; Lian, Kun; Li, Lihua; Wang, Qiang (Frontiers in Immunology, 2026)
N6-methyladenosine (m6A) is the most abundant post-transcriptional modification in eukaryotic mRNA, extensively involved in RNA splicing, export, stability, and translation. In recent years, accumulating evidence has demonstrated that m6A modification plays a critical role in regulating the differentiation and function of immune cells. Among these, myeloid-derived suppressor cells (MDSCs), as a key immunosuppressive population within the tumor microenvironment (TME), accelerate tumor progression by inhibiting T cell activity and promoting immune evasion and therapy resistance. Emerging studies indicate that m6A modification modulates the development, accumulation, and immunosuppressive function of MDSCs, thereby contributing to tumor initiation and progression. This review provides a narrative overview of the current evidence regarding the crosstalk between m6A modification and MDSCs, with a focus on the underlying molecular mechanisms and their potential implications for cancer immunotherapy. Furthermore, we discuss future research directions and the challenges associated with clinical translation.